Exploring the interplay of landscape changes and ecosystem services maximization in man-managed lagoon areas - Stocco, Alice; Dupré, Lorenzo; Pranovi, Fabio (Estuarine, coastal and shelf science, 2024)
Coastal lagoons have long been subject to continuous changes caused by mutual interactions with human activities. Monitoring such changes becomes critical, particularly when modifications in landscape and land cover classes can affect their capacity to ensure Ecosystem Services (ESs). In the Venice lagoon, some confined areas called “valli da pesca” supply provisioning ESs, namely aquaculture and hunting, but also other ESs important for the entire lagoon, such as regulating and cultural ones. Being heavily modified ecosystems under human control, valli da pesca underwent considerable morphological evolution depending on the maximized ES and the applied management. Using remote sensing data from different sources, we reconstructed changes in land cover and landscape elements in valli da pesca over the last century. By calculating landscape indicators related to land, saltmarshes, and water, we found that landscape features were initially similar for all the valli da pesca. Then, a process began between 1975 and 1987, in which management devoted to maximizing different ESs shaped the land cover in specific patterns. This study confirms the importance of these areas in the context of the entire lagoon and suggests the need to monitor their land cover changes to avoid the depletion of their capacity to conserve landscape elements and the related ESs. In this task, remote sensing data represents an important source of historical data that can deepen the knowledge about human-Nature interactions, capable of tracing the landscape evolution and the dynamics in the ESs supply as responses to human interventions. [Display omitted] •Aquaculture and hunting reserves of the Venice lagoon changed through the years.•Remote sensing data allows for multi-temporal landscape analyses.•Landscape indicators were effective in describing the valli da pesca evolution.•Human interventions influenced the landscape structure in order to maximize different ecosystem services.•Fish production and hunting cause different landscape arrangements to arise.